The Interactive Factors Contributing to Fear of Death - Mahdi Rezapour (Frontiers in Psychology, 2022)
Despite the importance of the topic of death, a limited comprehensive statistical analysis conducted highlighting the complex association between fear of death and various variables. Thus, this study is conducted to account for the possible complexity by considering all interaction terms after reducing the dimensionality of a dataset by means of recursive feature elimination, followed by the removal of the multi-collinear variables. The results highlighted, for instance, although being married, older and female offset the negative associations of fear of death, their impacts are multiplicative. Also, those who think cryonics is desirable are associated with higher fear of death. For instance, while belief in cryonics is positively associated with fear of death, its association varies depending on the trouble that individuals experience that someday they would not be alive and their marital status.